The role of alexithymia and empathy on radiation therapists' professional quality of life. (September 2020) - Franco, Pierfrancesco; Tesio, Valentina; Bertholet, Jenny; Gasnier, Anne; Gonzalez del Portillo, Elisabet; Spalek, Mateusz; Bibault, Jean-Emmanuel; Borst, Gerben; Van Elmpt, Wouter; Thorwarth, Daniela; Mullaney, Laura; Røe Redalen, Kathrine; et al.
Highlights: Professional quality of life is crucial for oncology professionals. Alexythymia and empathy affect the individual capacity to cope with stress. Alexythimia has a negative impact on radiation therapists' professional quality of life. Higher empatic concern increases the quality of professional well-being. This data may help targeting professionals at risk to implement preventive strategies. Abstract: Background and purpose: Physical and mental well-being are crucial for oncology professionals as they affect performance at work. Personality traits, as alexithymia and empathy, may influence professional quality of life. Alexithymia involves diminished skills in emotion processing and awareness. Empathy is pertinent to the ability to understand another's 'state of mind/emotion'. The PROject on Burn-Out in RadiatioN Oncology (PRO BONO) investigates professional quality of life amongst radiation oncology professionals, exploring the role of alexithymia and empathy. The present study reports on data pertinent to radiation therapists (RTTs). Material and methods: An online survey targeted ESTRO members. Participants were asked to fill out 3 questionnaires for alexithymia, empathy and professional quality of life: (a) Toronto Alexithymia Scale (TAS-20); (b) Interpersonal Reactivity Index (IRI); (c) Professional Quality of Life Scale (ProQoL). The present analysis focuses on RTTS to evaluate compassion satisfaction (CS), secondary traumatic stress (STS) and Burnout and their correlation with alexithymia and empathy, using generalized linear modeling. Covariates found significant at univariate linear regression analysis were included in the multivariate linear regression model. Results: A total of 399 RTTs completed all questionnaires. The final model for the burnout scale of ProQoL found, as significal predictors, the TAS-20 total score ( β  = 0.46, p  < 0 0.001), and the individual's perception of being valued by supervisor ( β  = −0.29, p  < 0.001). With respect to CS, the final model included TAS-20 total score ( β  = −0.33, p  < 0.001), the Empatic Concern domain ( β  = 0.23, p  < 0.001) of the IRI questionnaire and the individual's perception of being valued by colleagues ( β  = 0.22, p  < 0.001). Conclusions: Alexithymia increased the likelyhood to experience burnout and negatively affected the professional quality of life amongst RTTs working in oncology. Empathy resulted in higher professional fulfillment together with collegaues' appreciation. These results may be used to benchmark preventing strategies and implement organization-direct and/or individual-directed interventions.